Examining indicators of psychosocial risk and resilience in parents of autistic children - Dimachkie Nunnally, Amanda; Factor, Reina S.; Sturm, Alexandra; Valluripalli Soorya, Latha; Wainer, Allison; Taylor, Sandra; Ponzini, Matthew; Abbeduto, Leonard; Gulsrud, Amanda C. (Frontiers in Behavioral Neuroscience, 2023)
Background Parents of autistic children experience increased levels of caregiver strain and adverse mental health outcomes, even in comparison to parents of children with other neurodevelopmental disabilities. Previous studies have largely attributed these increased levels of mental health concerns to their child behavioral concerns and autism symptomatology, but less attention has been given to other potential child factors, such as child adaptive functioning. Additionally, little is known about potential protective factors, such as parents’ emotion regulation (ER) abilities, that may ameliorate the experience of caregiver strain, anxiety, and depression. Objective The current study examined the impact of child characteristics (restricted and repetitive behaviors, adaptive functioning and behavioral concerns) on parent mental health outcomes (caregiver strain, anxiety, depression and wellbeing). Additionally, we explore parents’ ER abilities as a moderator of the impact of child characteristic on parents’ mental health outcomes. Results Results of linear mixed effect models indicated a significant relationship between parents’ ER abilities and all four parent outcomes. Additionally, children’s adaptive functioning abilities and repetitive behaviors (RRBs) were significant predictors of caregiving strain. Parents’ ER abilities were a significant moderator of the effect of children’s repetitive behaviors and adaptive functioning challenges on caregiver strain, such that better ER abilities mitigated the impact of child clinical factors on caregiver strain. Finally, a significant difference was detected for mothers’ and fathers’ mental health, with mothers reporting higher caregiver strain, and more symptoms of anxiety and depression than did fathers. Conclusion This study leveraged a large sample of autistic children and their biological parents to examine the relationship between children’s clinical characteristics and parents’ psychological wellbeing. Results indicate that, although parents of autistic children do experience high rates of internalizing mental health concerns that relate to child adaptive functioning and RRBs, parent ER abilities act as a protective factor against parents’ adverse mental health outcomes. Further, mothers in our sample reported significantly higher rates of depression, anxiety, and caregiver strain, as compared with fathers.